WORKSHOP ON MAKING FINANCIAL STATEMENTS TO INCREASE DATA INDEPENDENCE IN THE DIGITAL ERA FOR INDONESIAN MSMES - Sumarsid Sumarsid; Hartatik Hartatik; Khaeruman Khaeruman; Ahmad Mukhlis; Suflani Suflani; Lilis Suryani (Yayasan Education and Social Center, 2022)
In developing Small and Medium Micro Enterprises (MSMEs) it is necessary to know the performance of its business in view of its business financial statements. The problem that exists today is that the majority of MSMEs in Indonesia do not make financial statements because of various things, namely busyness in trying and not knowing how to make financial statements. The results of interviews and surveys to 100 MSMEs in Indonesia in February are that almost all MSMEs do not know how to make basic or simple financial statements. So we as Pengabdi aim to provide knowledge of making simple financial statements by providing training and assistance in making digital financial statements with the help of Smartphones, due to the flexibility of time and place in its manufacture. The method provided by way of 1.Training in making simple financial statements for MSMEs, 2.Training and assistance in making android-based digital accounting in Smartphones. The results of the workshop of MSME participants who follow the spirit of practice and can make financial statements on their respective Smartphones